2018
DOI: 10.3897/natureconservation.27.23728
|View full text |Cite
|
Sign up to set email alerts
|

Seed plant features, distribution patterns, diversity hotspots, and conservation gaps in Xinjiang, China

Abstract: R (2018) Seed plant features, distribution patterns, diversity hotspots, and conservation gaps in Xinjiang, China. Nature Conservation 27: 1-15. https://doi. org/10.3897/natureconservation.27.23728 AbstractThe flora in Xinjiang is unique. Decisions about biodiversity conservation and management based on seed plant diversity hotspots and conservation gaps in Xinjiang are essential to maintain this unique flora. Based on a species distribution dataset of seed plants, we measured seed plant diversity using specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In addition, all species of Betula within Xinjiang mostly distribute in Tianshan Mountain and Altai Mountain. The diversity hotspots of seed plants of Xinjiang are mainly located in both of these two mountains (Huang et al 2018). Therefore, the main distribution area of Betula in Xinjiang is consistent with the diversity distribution centre of plant species in Xinjiang.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…In addition, all species of Betula within Xinjiang mostly distribute in Tianshan Mountain and Altai Mountain. The diversity hotspots of seed plants of Xinjiang are mainly located in both of these two mountains (Huang et al 2018). Therefore, the main distribution area of Betula in Xinjiang is consistent with the diversity distribution centre of plant species in Xinjiang.…”
Section: Introductionsupporting
confidence: 66%
“…In Xinjiang, there are a small number of tropical families or genera in the distribution area of congeneric species of B. halophila, which may be a legacy of flora under a hot climate in the early Tertiary in Xinjiang (Pan 1995). To some extent, it also reflects the uniqueness of the seed plant flora distributed in the distribution area of congeneric species of B. halophila, just like the uniqueness of seed plant flora in Xinjiang (Huang et al 2011;Huang et al 2018). Nearly 94% of the families of Xinjiang are found in the distribution area of congeneric species of B. halophila, which indicates the distribution areas of these species cover the diversity distribution centre of seed plants in Xinjiang.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this study, most of the hotspots neglected by the SR index were identified by the SC index, indicating that these “species‐poor” hotspots are also important for biodiversity conservation. This is especially the case for the Changbai Mountains (hotspot 1) and the mountainous areas in north Xinjiang, which play an important role in conserving native species (Wan et al, 2014; Huang et al, 2018). The hotspots derived by WE focus on the areas that are characterized by range‐restricted species, were similar to the SR‐based hotspots.…”
Section: Discussionmentioning
confidence: 99%
“…A large part of the region is arid and semiarid, and onesixth is covered by desert [3]. Due to the characteristics of its special geographical location, Xinjiang has become a biodiversity hotspot with high species richness and endemic levels, especially breeding many drought-tolerant insect species [8][9][10][11]. For example, 84 species of Meloidae Gyllenhal, 1810, accounting for approximately 40% of the total number of species occurring in China, were recorded in Xinjiang [12].…”
Section: Introductionmentioning
confidence: 99%